Limits and binomial theorem

Calculus Level 5

lim n ( 1 + r = 1 n 1 3 r r ! i = 1 r ( 2 i 1 ) ) = ? \lim_{n\to\infty} \left(1 + \sum_{r=1}^n \frac 1{3^r r!} \prod_{i=1}^r (2i - 1) \right )= \, ?


The answer is 1.73.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Chew-Seong Cheong
Aug 24, 2020

S = 1 + r = 1 1 3 r r ! i = 1 r ( 2 i 1 ) = 1 + r = 1 ( 2 r 1 ) ! ! 3 r r ! = 1 + r = 1 ( 2 r ) ! 3 r 2 r ( r ! ) 2 = 1 + r = 1 ( 2 r r ) 1 6 r Since n = 0 ( 2 n n ) x n = 1 1 4 x = r = 0 ( 2 r r ) 1 6 r = 1 1 2 3 = 3 1.73 \begin{aligned} S & = 1 + \sum_{r=1}^\infty \frac 1{3^r r!}\prod_{i=1}^r (2i-1) \\ & = 1 + \sum_{r=1}^\infty \frac {(2r-1)!!}{3^r r!} \\ & = 1 + \sum_{r=1}^\infty \frac {(2r)!}{3^r \cdot 2^r (r!)^2} \\ & = 1 + \sum_{r=1}^\infty \binom {2r}r \cdot \frac 1{6^r} & \small \blue{\text{Since }\sum_\red{n=0}^\infty \binom {2n}n x^n = \frac 1{\sqrt{1-4x}}} \\ & = \sum_\red{r=0}^\infty \binom {2r}r \cdot \frac 1{6^r} \\ & = \frac 1{\sqrt{1-\frac 23}} = \sqrt 3 \approx \boxed{1.73} \end{aligned}

so hard . wish to learn one day.. soon

Victor Taylor - 9 months, 2 weeks ago

Log in to reply

Yes, keep it up.

Chew-Seong Cheong - 9 months, 2 weeks ago

Did the same way....

Nikola Alfredi - 9 months, 2 weeks ago

You are just guessing it is a power series, it won't work if it does not. Chew-Seong Cheong's solution is better.

Isaac YIU Math Studio - 9 months, 3 weeks ago

Log in to reply

His guess that it is a power series is justified because the terms when rearranged are taking the form of the central binomial coefficient(if we cosider the 3^r as just x^r). So a power series in terms of binomal theorem for any index is a good guess. Not to mention that the solution @Chew-Seong Cheong has used is the taylor expansion of 1 1 2 x \frac{1}{\sqrt{1-2x}} . Now the coefficients are indeed the binomial coefficient which is generalized for any n. So there is nothing wrong with this solution. The general term of the binomial expansion of 1 1 2 x \frac{1}{\sqrt{1-2x}} is x r ( 2 r 1 ) ! ! r ! \frac{x^{r}(2r-1)!!}{r!} , r > 0 r>0

Arghyadeep Chatterjee - 9 months, 3 weeks ago
Monu Kumar
Aug 29, 2020

given series can be written as

S = r = 0 ( 2 r r ) 1 6 r \begin{aligned}S = \sum_{r=0}^{\infty} \binom{2r}{r} \frac{1}{6^{r}} \end{aligned}

which is equal to the coeffcient of x 0 x^{0} in the expansion of

f ( x ) = k = 0 ( 1 x + x 6 ) 2 k \begin{aligned}f(x) = \sum_{k=0}^{\infty}\left(\frac{1}{x} +\frac{x}{6}\right)^{2k} \end{aligned}

and for 0 < ( 1 x + x 6 ) < 1 \begin{aligned}0<|\left(\frac{1}{x} +\frac{x}{6}\right)|<1\end{aligned}

f ( x ) = 1 1 ( 6 + x 2 6 x ) 2 \begin{aligned}f(x)=\frac{1}{1-\left(\frac{6+x^{2}}{6x}\right)^{2}}\end{aligned}

f ( x ) = 36 x 2 x 4 24 x 2 + 36 \begin{aligned}f(x)=\frac{-36 x^{2}}{x^{4}-24x^{2}+36}\end{aligned}

f ( x ) = 36 x 2 ( x 2 α ) ( β x 2 ) \begin{aligned}f(x)=\frac{36 x^{2}}{(x^{2}-\alpha)(\beta-x^{2})}\end{aligned}

f ( x ) = 36 x 2 α β ( 1 x 2 α + 1 β x 2 ) \begin{aligned}f(x)=\frac{36 x^{2}}{\alpha-\beta}\left(\frac{1}{x^{2}-\alpha}+\frac{1}{\beta-x^{2}}\right)\end{aligned}

f ( x ) = 36 α β ( 1 1 α x 2 + x 2 β ( 1 x 2 β ) ) \begin{aligned}f(x)=\frac{36 }{\alpha-\beta}\left(\frac{1}{1-\frac{\alpha}{x^{2}}}+\frac{x^{2}}{\beta(1-\frac{x^{2}}{\beta})}\right)\end{aligned}

f ( x ) = 36 α β k = 0 ( ( α x 2 ) k + ( x 2 β ) k + 1 ) \begin{aligned}f(x)=\frac{36 }{\alpha-\beta}\sum_{k=0}^{\infty}\left(\left(\frac{\alpha}{x^{2}}\right)^{k}+\left(\frac{x^{2}}{\beta}\right)^{k+1}\right)\end{aligned}

coffcient of x 0 x^{0} is 36 α β \begin{aligned}\frac{36}{\alpha- \beta}\end{aligned} and α β = 12 3 \alpha- \beta =12\sqrt{3}

so answer is 3 \sqrt{3}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...